2019
DOI: 10.1016/j.midw.2019.102531
|View full text |Cite
|
Sign up to set email alerts
|

New understandings of fathers’ experiences of grief and loss following stillbirth and neonatal death: A scoping review

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 39 publications
2
49
3
4
Order By: Relevance
“…However, a low Cronbach's alpha was observed for the Toughness subscale of the MRNI. Although this measure of 'toughness' did not emerge as a signi cant predictor in any of the models in the current study, it may still be an important factor to consider, as a low alpha value may indicate that this measure did not adequately capture men's experiences of needing to be 'strong' or 'tough' as reported in previous qualitative studies [10,12,13,31,36]. Future research could explore alternative ways to measure this construct and assess whether it is important in explaining men's grief.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, a low Cronbach's alpha was observed for the Toughness subscale of the MRNI. Although this measure of 'toughness' did not emerge as a signi cant predictor in any of the models in the current study, it may still be an important factor to consider, as a low alpha value may indicate that this measure did not adequately capture men's experiences of needing to be 'strong' or 'tough' as reported in previous qualitative studies [10,12,13,31,36]. Future research could explore alternative ways to measure this construct and assess whether it is important in explaining men's grief.…”
Section: Discussioncontrasting
confidence: 50%
“…Broader research on grief also demonstrates potential differences in grief styles for men and women, with a general classi cation made between instrumental (action-focused coping) and intuitive (emotionfocused coping) styles [27]. Following pregnancy loss and neonatal death, studies suggest that men may engage in more instrumental grieving styles, which includes using activities, distraction or problemsolving approaches to grief, as opposed to intuitive styles which use emotion-focused approaches including outward displays of crying, talking about grief, or seeking social support [9,16,[28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Health professionals and the community ignore and disallow the father´s grieving for PD although it has been shown that PD does have repercussions for fathers [46]. It is necessary to determine the needs of fathers [51,52] and clearly recognize their grief [38,39,47,53]. Although the sample of fathers in this study as more limited than that of mothers, our study investigates the experiences and perceptions of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Worden included such environmental factors as "mediator 6: social variables" [36]. Although the individual implications of perinatal death on the parents [11][12][13][14][15][16][17][18] and the social support available to survivors [37] have been extensively investigated, there is a lack of research involving fathers [38,39]. Moreover, the impact of PD on the social environment and the extended family has been poorly investigated [40].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three reviews were published in areas relating to men's experiences of pregnancy/neonatal loss. However, two of these were scoping reviews rather than systematic [48,49], and the other thematically synthesised only qualitative studies on men's lived experiences of miscarriage [50]. This systematic review aimed to provide a comprehensive summary and appraisal of existing qualitative and quantitative literature on men's grief, following both pregnancy loss and neonatal loss.…”
Section: Previous Literature On Grief Following Pregnancy Loss and Nementioning
confidence: 99%